Receptores solúveis do fator de necrose tumoral como preditores de mortalidade e disfunção renal após transplante hepático - Bruno Salome de Morais (2014)
Background: several risk factors influence survival after liver transplantation (LT). The primary aim of this study was to determine the value of perioperative soluble Tumor Necrosis Factor Receptors (sTNF-R) in predicting renal dysfunction or mortality after LT. Some researches have shown the relationship between sTNFR1 and sTNFR2 with worse clinical liver disease outcome, but there is no data showingassociation between sTNF-R and outcome after LT. We believe that the knowledge of immune stimulation level with perioperative measure of sTNF-R may predict worse outcome following LT. Methods. Data were collected prospectively from 122 patients submitted to cadaveric orthotopic LT from September 2008 to December 2011. The blood samples were collected in 7 different perioperative times (betweenanesthesia induction and surgery incision T1; before portal vein clamp T2; 5 minutes before graft reperfusion T3; 15 minutes after graft reperfusion T4; 2 hours after graft reperfusion T5; 8 hours after graft reperfusion T6 and 24 hours after graft reperfusion T7) and analyzed by Enzyme-linked immunoabsorbent assay (ELISA) method. The statistical analysis included a screening univariate analysis followed by a stepwise logistic regression. The predictive value of significant variables was assessed by means of the receiver-operator characteristic (ROC) curve. Results. One month and 1 year LT survival was 91% and 81%,respectively. Postoperative renal dysfunction incidence was 17%. Each 1000 pg/ml sTNF-R1 increase after 24h of graft perfusion is associated to postoperative renal replacement therapy (RRT) (OR 1.25) and 1 year mortality (OR 1.1). RRT was strongly associated to 30 days and 1-year LT mortality, OR 19,78 and 45,45, respectively. Conclusion. Higher sTNF-R1 levels 24 hours after graft perfusion are independent predictors of RRT and 1-year mortality after. RRT is a predictor of 30 days and 1 year mortality after LT.